Intende, lector : echoes of myth, religion and ritual in the ancient novel - Futre Pinheiro, M. (Marília); Bierl, Anton, 1960- (MythosEikonPoiesis ;, 2013)
Despite the recent and intensified scholarly interest in the field of myth and ritual, inquiry into major shifts in mythical and ritual poetics is still in a preliminary stage. The essays in this collection advance our understanding considerably as they probe the intersections of myth and ritual with the plot of the novels. The volume provides a substantial point of departure for subsequent research into freer models of interaction between literature and religion.